Considering the food environment can help to promote the consumption of aquatic foods for healthy diets - Kennedy, Gina; Ahern, Molly B.; Iannotti, Lora L.; Vie, Sydney; Sherburne, Lisa; Thilsted, Shakuntala H. (Frontiers in Sustainable Food Systems, 2023)
Aquatic foods ensure food and nutrition security for billions of consumers around the world. As part of food systems, aquatic foods provide nutritious, affordable, convenient options for healthy diets, and can also foster sustainable food production. Within the food system framework, the food environment is the space that connects food procurement to consumption. The food environment influences consumer decisions on which foods to acquire. To date there has been relatively little focus on creating an enabling food environment that supports consumers in decisions to obtain aquatic foods. To fill this gap, we conducted a narrative review of literature from 2000-2020 to document the availability, affordability, convenience, promotion, quality, and sustainability of aquatic foods within diverse food environments. Our review highlighted several opportunities that can support development and promotion of convenient, high quality aquatic foods. We also noted several research gaps. For example, some consumers, especially those in high income countries, respond well to labels related to sustainability and also to messaging to consume diverse types of fish, especially lower tropic species like anchovy. However, less is documented on how promotion influences consumers from LMIC. The paper also notes a gap in assessment of the price and affordability of aquatic foods. Most price and affordability assessments do not provide details on which aquatic foods were considered in the costing assessment. In addition, wild or home-harvested aquatic foods are often not accounted for in price and affordability assessments. Using case studies, we demonstrate how considering the food environment in research and implementation strategies can add value to program design. For example, processing tuna frames and underutilized small fish species into powder is one innovation that reduces food waste and also creates a convenient, quality product. These results provide the foundation for deepening our understanding of how key elements of the food environment influence consumers’ decision-making and how these elements can be considered in future research, programming and policy efforts.